Этнос в предметной области социальной философии - Емельянова, Юлия Павловна; Ємельянова, Юлія Павлівна; Yemelianova, Yuliia P. (Східноєвропейський національний університет імені Лесі Українки, 2014)
В статье рассматривается проблема теоретического определения этноса в предметной области социальной философии и социальной теории. Предлагается возможная стратегия исследования этнических процессов, а также обосновывается необходимость логико-философского обобщения массива знаний по этому вопросу, накопленных в науке о человеке. Сущность и роль этноса как субъекта социальной реальности анализируется с позиции интегрального подхода и теории организации. The author studies the problem of a theoretical definition of ethnos as a subject of social philosophy and social theory and suggests a possible research strategy of ethnical processes. The necessity of logical-philosophical generalisation of extensive knowledge accumulated by various branches of human science is grounded in this article. The nature and the role of ethnos as a subject of social reality is could be studied from the position of integral approach and organizational theory. The author’s grounds is an implication that the solution of a given problem by the methods of modern social- humanitarian knowledge may assist the resolution of the modern world's social-political problems.
Ethnos in a Discipline (Object) of Social Philosophy
Keywords: социальная реальность; общество; этнос; субъект социальный; этническая организация; Social reality; society; ethnos; social subject; ethnic(al) organization